Low temperature deformation of MoSi2 and the effect of Ta, Nb and Al as alloying elements - Zenk, Carolin; Gibson, James S.K.L.; Maier-Kiener, Verena; Neumeier, Steffen; Göken, Mathias; Korte-Kerzel, Sandra (Acta Materialia, 2019)
Molybdenum disilicide (MoSi2) is a very promising material for high temperature structural applications due to its high melting point (2030∘C), low density, high thermal conductivity and good oxidation resistance. However, MoSi2 has limited ductility below 900∘C due to its anisotropic plastic deformation behaviour and high critical resolved shear stresses on particular slip systems. Nanoindentation of MoSi2 microalloyed with aluminium, niobium or tantalum showed that all alloying elements cause a decrease in hardness. Analysis of surface slip lines indicated the activation of the additional 1 1 0<1 1 1> slip system in microalloyed MoSi2, which is not active below 300∘C in pure MoSi2. This was confirmed by TEM dislocation analysis of the indentation plastic zone. Further micropillar compression experiments comparing pure MoSi2 and the Ta-alloyed sample enabled the determination of the critical resolved shear stresses of individual slip systems even in the most brittle [0 0 1] crystal direction.
CRIS-Team Scopus Importer:2019-10-22
Keywords: Dislocations; Micropillar compression; Molybdenum disilicide; Nanoindentation; Plasticity